Peran Media dalam Mempromosikan Kesadaran Tentang OPM dan Hak Asasi Manusia di Papua - Khoirunnisa’, Melta Bintang Aulia, Hamdiah; Nur Azizah, Happy Salwa; Maharani, Indri Althafah; Ivana, Novelia Nashrul; Nur Amalina, Talita; Abishta, Mareta Atha Niar; Fahdany, Zahra Aulia; Pangestu, Yogi Wahyu; Susanto, Tantut (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
One of the reasons Papua is prone to conflict is because it cannot be separated from the return of Papua to Indonesia. Injustices such as access to education, health and infrastructure are also very limited so that they feel marginalized and cause tensions between the government and local communities. This event resulted in the emergence of separatist movements such as the Free Papua Organization (OPM). Conflicts and social problems in Papua have influenced the social image of Papuans, namely the negative stigma. The media is needed to help raise public awareness about human rights violations, give a voice to victims, and educate the public about issues in the region. The media can be a link between Papuans and the outside world, increasing international support for their rights. The survey results show that the media, especially social media, has a major influence in shaping public awareness about the OPM and human rights in Papua. However, there is an urgent need to improve the quality of reporting, provide more in-depth information, and emphasize educational aspects related to the roots of the conflict and more holistic solutions. Thus, the media can play a more strategic role in creating balanced and constructive awareness among the public